Articulating the entrepreneurship career: A study of German women entrepreneurs. (August 2017) - Braches, Birgit; Elliott, Carole
This article examines how German women construct accounts of entrepreneurship as a gendered career. While becoming an entrepreneur was deemed preferable to not having a career, the interpretative repertoires emerging around entrepreneurial careers mainly referred to structural barriers. These included 'anti-child anti-woman' attitudes within German society or acceptance of the 'male game' due to gendered role expectations embedded within social institutions. Interpreted from a career perspective, the findings indicate that entrepreneurial careers do not meet women's expectations as they are subject to the same gendered constraints as those faced in waged employment. The article contributes to boundaryless career theory by illustrating how, even within a country of high employment rates and talent shortage, Germany's status as a conservative welfare state builds gender inequality into entrepreneurial women's lives to constrain career choices.